2022
DOI: 10.1093/texcom/tgac018
|View full text |Cite
|
Sign up to set email alerts
|

Boosting working memory: uncovering the differential effects of tDCS and tACS

Abstract: Working memory (WM) is essential for reasoning, decision making and problem solving. Recently, there has been an increasing effort in improving WM through non-invasive brain stimulation, especially transcranial direct and alternating current stimulation (tDCS/tACS). Studies suggest that tDCS and tACS can modulate WM performance, but large variability in research approaches hinders identification of optimal stimulation protocols and interpretation of study results. Moreover, it is unclear whether tDCS and tACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 97 publications
(185 reference statements)
0
7
0
Order By: Relevance
“…Specifically, our actflow model-based analysis complements previous studies characterizing the role of DLPFC in working memory ( Cai et al, 2021 ; Finn et al, 2019 ; Mencarelli et al, 2019 ; Senkowski et al, 2022 ) by revealing influences from default mode and frontoparietal networks that likely drive DLPFC’s involvement in n-back cognitive processes. Further, actflow models allowed us to estimate the degree to which distributed afferent processes—as opposed to recurrent within-region processes—play a role (47% of n-back contrast inter-subject variance explained) in right DLPFC working-memory-related activity.…”
Section: Discussionmentioning
confidence: 62%
“…Specifically, our actflow model-based analysis complements previous studies characterizing the role of DLPFC in working memory ( Cai et al, 2021 ; Finn et al, 2019 ; Mencarelli et al, 2019 ; Senkowski et al, 2022 ) by revealing influences from default mode and frontoparietal networks that likely drive DLPFC’s involvement in n-back cognitive processes. Further, actflow models allowed us to estimate the degree to which distributed afferent processes—as opposed to recurrent within-region processes—play a role (47% of n-back contrast inter-subject variance explained) in right DLPFC working-memory-related activity.…”
Section: Discussionmentioning
confidence: 62%
“…First, the current study selected the bilateral parietal cortex as the stimulus target, which has been demonstrated to be significantly associated with inhibitory control performance during cross-modal conflict (Cui et al 2022;Sawamura et al 2022). They also recruited the region associated with inhibitory control (i.e., DLPFC, rIFG), while they commonly used a lower current intensity (1 mA), indicating that stronger stimulation may be required to modulate excitability and cognitive performance (Senkowski et al 2022). In addition, we recruited hf-tRNS, while Brauer et al ( 2018) used full frequency tRNS, indicating that the high frequency is responsible for this excitability increase in tRNS stimulation (van der Groen et al 2022;Harty et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tDCS did not demonstrate significant differences from sham in any of the cognitive test scores. In addition, a recent review by Senkowski et al [119] compared the effects of tDCS and tACS on working memory (WM) in healthy adults, drawing from 43 studies. Results indicated a limited impact of single-session tDCS on WM, while tACS demonstrated frequency-dependent effects, particularly with frontoparietal stimulation.…”
Section: Challenges In Transcranial Electrical Stimulation (Tes)mentioning
confidence: 99%
“…A potential advantage of tACS lies in the selection of stimulation frequency, aimed at modulating task-relevant physiological processes. In contrast to tDCS, whose effects are primarily contingent upon electrode placement and current intensity, tACS introduces an additional dimension through the manipulation of the stimulation frequency [119]. The effects of stroke on neural oscillations depend on the damage's severity and location.…”
Section: Advantages Of Using Tacs/trns In Cortical Excitability Modul...mentioning
confidence: 99%